Osteitis in Systemic Sclerosis: A Nationwide Case–Control Retrospective Study. Issue 5 (16th March 2022) - Cosse, Cyril; Kernéis, Solen; Lescoat, Alain; Pugnet, Gregory; Truchetet, Marie‐Elise; Priollet, Pascal; Diot, Elisabeth; Martin, Mickael; Maurier, François; Viallard, Jean François; Agard, Christian; Granel, Brigitte; et al.
Abstract : Objective: Systemic sclerosis (SSc) is an autoimmune connective tissue disorder characterized by skin fibrosis, vasculopathy, and dysimmunity. Data regarding osteitis in SSc are scarce. Methods: We performed a nationwide multicenter, retrospective, case–control study including patients with SSc, according to the 2013 American College of Rheumatology/European Alliance of Associations for Rheumatology classification, with a diagnosis of osteitis. The objectives of the study were to describe, to characterize, and to identify associated factors for osteitis in patients with SSc. Results: Forty‐eight patients were included. Twenty‐six patients (54.1%) had osteitis beneath digital tip ulcers. Physical symptoms included pain (36 of 48, 75%), erythema (35 of 48, 73%), and local warmth (35 of 48, 73%). Thirty‐one (65%) patients had median (interquartile range) C‐reactive protein levels >2 mg/liter of 8 (2.7–44.3) mg/liter. On radiography, computed tomography, or magnetic resonance imaging, osteitis was characterized by swelling or abscess of soft tissues, with acro‐osteolysis or lysis in 28 patients (58%). Microbiological sampling was performed in 45 (94%) patients. Most pathogens were Staphylococcus aureus (43.8%), anaerobes and Enterobacteriaceae (29.1%), and Pseudomonas aeruginosa (10.4%). Management comprised antibiotics in 37 (77.1%) patients and/or surgery in 26 (54.2%). Fluoroquinolones were used in 22 (45.8%) patients, and amoxicillin plus β‐lactamase inhibitor in 7 (14.6%). Six (12.6%) patients relapsed, 6 (12.6%) patients had osteitis recurrence, 15 (32%) sequelae, and 2 patients had septic shock and died. Conclusion: This study confirmed digital tip ulcers as an associated factor for osteitis and revealed a high rate of functional sequelae. Antimicrobial therapy with oral fluoroquinolone or intravenous amoxicillin and β‐lactamase inhibitor are used as first‐line antibiotic therapy in SSc patients with osteitis.